(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
The Neogene sedimentary sequence of Capo Milazzo (NE Sicily) has been analyzed in detail. Interest has been focused on the stratigraphic interval comprised between the metamorphic basement and the Pliocene units, which documents the response of a coastal area to the complex events that affected the Mediterranean basin during the Late Miocene.